Peran Artifical Intelligence (AI) dalam Layanan Konseling Online: Peluang, Tantangan, dan Implikasi Etis (Studi Literature) - Fatma Maylasari Saqoti (PT. PENERBIT TIGA MUTIARA, 2026)
The advancement of digital technology has encouraged the adoption of Artificial Intelligence (AI) in online counseling services to enhance the accessibility and quality of mental health care. The emergence of AI through chatbots, virtual counselors, and digital mental health platforms presents various opportunities, challenges, and ethical implications that require comprehensive examination. This study aims to analyze the opportunities offered by AI, the challenges associated with its implementation, and the ethical implications of its use in online counseling services. The study employed a literature review method with a qualitative approach, examining 15 scientific articles published between 2016 and 2026. Data were analyzed using content analysis through the synthesis of findings from previous studies. The results indicate that AI has the potential to expand access to counseling services, improve service efficiency, support preliminary assessments, and facilitate the delivery of more personalized and data-driven interventions. However, the use of AI continues to face several challenges, including limitations in understanding human emotions and social contexts, the risk of inaccurate responses, algorithmic bias, and the potential for user dependency on technology. The most prominent ethical concerns involve privacy protection, data security, algorithmic transparency, system accountability, and professional responsibility. This study concludes that AI is more appropriately positioned as a supportive tool or co-counselor for professional counselors rather than a replacement for human practitioners. The novelty of this study lies in its integration of the opportunities, challenges, and ethical implications of AI into a comprehensive analytical framework.